A literary perspective of the colonial medicine from the XVIth century: Tratado breve de medicina of fray Agustín Farfán. - Cortés Guadarrama, Marcos (2015)
Tratado breve de medicina (1592) of fray Agustín Farfán is one of the first medical guides of America. The present article considers that this medical writing uses rhetorical resources that approximates it to the colonial literature of the XVIth century, which, in turn, inherits some of its intrinsic features from the Spanish medieval literature. Based on this hybrid mark, there is a reflection on the concept of the invention of America, starting with the treatment that the author offers to disease and healing, melancholy being one of the most unique cases, since its social impact was determining for the colonial society of the time.